Variable induction of vitellogenin genes in the varroa mite, Varroa destructor (Anderson & Trueman), by the honeybee, Apis mellifera L, host and its environment. Issue 1 (18th January 2013) - Cabrera Cordon, A. R.; Shirk, P. D.; Duehl, A. J.; Evans, J. D.; Teal, P. E. A.
Abstract: Transcript levels of vitellogenins (Vgs) in the varroa mite, V arroa destructor (Anderson & Trueman), were variably induced by interactions between the developing honeybee, Apis mellifera L, as a food source and the capped honeybee cell environment. Transcripts for two Vgs of varroa mites were sequenced and putative Vg protein products characterized. Sequence analysis of Vd Vg1 and Vd Vg2 proteins showed that each had greater similarity with Vg1 and Vg2 proteins from ticks, respectively, than between themselves and were grouped separately by phylogenetic analyses. This suggests there was a duplication of the ancestral acarine Vg gene prior to the divergence of the mites and ticks. Low levels of transcript were detected in immature mites, males and phoretic females. Following cell invasion by phoretic females, Vd Vg1 and Vd Vg2 transcript levels were up‐regulated after cell capping to a maximum at the time of partial cocoon formation by the honeybee. During oviposition the two transcripts were differentially expressed with higher levels of Vd Vg2 being observed. A bioassay based on assessing the transcript levels was established. Increases in Vd Vg1 and Vd Vg2 transcripts were induced experimentally in phoretic females when they were placed inside a cell containing an early metamorphosing last instar bee but not when exposed to the metamorphosing bee alone. The variable response of Vg expression to the food source as well as environmental cues within the capped cell demonstrates that perturbation of host−parasite interactions may provide avenues to disrupt the reproductive cycle of the varroa mites and prevent varroasis.